A study of leguminosae bacteria - Stanfield, William Wesley (My University, 1905)
Introduction: A complete study of leguminosae bacteria would involve the consideration of many questions beyond the present ability of the writer while at the same time the briefest discussion of the points thus brought under consideration would prolong the extent of this paper beyond reasonable limits. It is not, therefore, my object to present a full discussion of the subject, but briefly to review some of the chief factors appertaining thereto. As an introduction to this study it will probably be well to speak of the economic importance of leguminosae bacteria. It has long been known to agricultural investigators that the most essential elements of plant food .are three in number, viz.; nitrogen, potassium, and phosphorus. Other elements are required, but in such small quantities and are almost everywhere present in such abundance that they may here be neglected. Potassium and phosphorus being products of the chemical disintegration of rock and soil are also relatively abundant, and, in addition are not easily soluble but combine readily with the bases in the soil and are not likely to become exhausted to such an extent as to cause serious apprehension on the part of the agriculturist. Not so, however, with nitrogen. A. careful calculation by competent authority reveals the fact that while in the first eight inches of average soil in the United States there is, were it possible for all of the essential elements to be assimilated without waste, sufficient potential phosphoric acid for 129, and potash for 240 crops of maize of 50 bushels per acre each, there is nitrogen present sufficient for only 32 such crops. Nitrogen is the most essential element to the growth of living tissue, be it plant or animal, and in addition is the scarcest and the most liable to depreciation and loss. The question of the nitrogen supply is therefore of paramount importance not only to the agriculturist but to the world at large
A study of legtuinosac bacteria and experiments relative to adapting them to non-leguminous plants
Citation: Stanfield, William Wesley. A study of leguminosae bacteria. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Nitrogen Essential for Living Tissue; Restoring Nitrogen to Soil; Theses